The Single-Period Inventory Model with Spectral Risk Measures - Fichtinger, Johannes (Forschungsergebnisse der Wirtschaftsuniversitaet Wien, 2012)
Inventory management and pricing decisions based on quantitative models both in industrial practice and academic works often rely on minimizing expected cost, which refers to the concept of risk-neutrality of the decision maker. Although many useful insights in operational problems can be obtained by such an approach, it is well understood that incorporating attitudes toward risk is an important lever for building new theories in other fields such as economics and finance. In this work spectral risk measures are applied to the price-setting newsvendor problem and optimal policies are derived. This allows to unify results obtained so far in the literature under the common concept of spectral risk measures for the case of zero and non-zero shortage penalty cost.